Analysis of Behavioral Factors on Medications in Gout Patients with Health belief Model Theory - Ika Ratna Hidayati (Journal of Global Pharma Technology, 2020)
Objective : To identify behavioral factor associated with medication adherence using the Health Belief Model theory. Methods : This study used a cross sectional approach with accidental sampling technique. The number of samples used 64 people. The instruments were used the adherence to refills medication scale and the Health Belief Model questionnaire which had been tested for validation and reliability on the questionnaire. Data were analysed using multiple linear regression analysis. Conclusions : Each Health Belief Model theory variables which are perceived susceptibility, perceived severity, perceived benefits, and perceived barriers had a significant effect on medication adherence in gout patients (p 0.05). The Health Belief Model Theory had coefficient determination (R2) 59.7%. This indicates that the Health Belief Model can predict the behavior of patients who adhere to treatment well. Keywords : Adherence, Health Belief Model, Gout, Community Health Center, Behavior